ChemInform Abstract: A New Convenient Synthetic Method and Preliminary Pharmacological Characterization of Triazinediones as Prokineticin Receptor Antagonists. Issue 48 (2nd December 2014) - Congiu, Cenzo; Onnis, Valentina; Deplano, Alessandro; Salvadori, Severo; Marconi, Veronica; Maftei, Daniela; Negri, Lucia; Lattanzi, Roberta; Balboni, Gianfranco
Abstract A new improved synthetic methodology to form triazinediones as potential antagonists for prokineticin receptors is described.